A homozygous AHI1 gene mutation (p.Thr304AsnfsX6) in a consanguineous Moroccan family with Joubert syndrome: a case report. (December 2015) - Chafai-Elalaoui, Siham; Chalon, Matthias; Elkhartoufi, Nadia; Kriouele, Yamna; Mansouri, Maria; Attié-Bitach, Tania; Sefiani, Abdelaziz; Baala, Lekbir
Abstract Introduction Joubert syndrome is a rare congenital disorder characterized by brain malformation, developmental delay with hypotonia, ocular motor apraxia, and breathing abnormalities. Joubert syndrome is a genetically highly heterogeneous ciliopathy disorder with 23 identified causative genes. The diagnosis is based on brain imaging showing the "molar tooth sign" with cerebellar vermis agenesis. We describe a consanguineous Moroccan family with three affected siblings (18-year-old boy, 13-year-old girl, and 10-year-old boy) showing typical signs of Joubert syndrome, and attempt to identify the underlying genetic defect in this family. Methods We performed genome-wide homozygosity mapping using a high-resolution array followed by targeted Sanger sequencing to identify the causative gene. Results This approach found three homozygous regions, one including theAHI1 gene. Direct sequencing of the 26 coding exons ofAHI1 revealed a homozygous mutation (p.Thr304AsnfsX6) located in exon 7 present in the three Joubert syndrome-affected Moroccan siblings. Of more interest, this truncating mutation was previously reported in patients with compound heterozygous Joubert syndrome originating from Spain (one patient) and from the Netherlands (two patients), suggesting a possible founder effect or mutational hotspot. Conclusions Combined homozygosity mapping and targeted sequencing allowed the rapid detection of the disease-causing mutation in theAHI1 gene in this family affected with a highly genetically heterogeneous disorder. Carriers of the same truncating mutation (p.Thr304AsnfsX6), originating from Spain and the Netherlands, presented variable clinical characteristics, thereby corroborating the extreme heterogeneity of Joubert syndrome.